Sampling locations and processing methods shape fungi microbiome on the surface of edible and medicinal Arecae semen - Wei, Guangfei; Xu, Jia; Zhang, Zhaoyu; Zhang, Guozhuang; Chen, Shilin; Dong, Linlin (Frontiers in Microbiology, 2023)
Arecae semen, which is derived from the dried ripe seed of Areca catechu L., has been commonly used as one of the major traditional Chinese medicines (TCMs). Three types of crude herbal preparations, namely, raw Arecae semen (AS), Arecae semen tostum (SAS), and Arecae semen carbonisata (FAS), are available for different clinical applications in TCMs. Although aflatoxin contamination in Arecae semen has been reported preliminarily, only a few studies have been conducted on fungal contamination. In this study, the presence of fungi on the surface of three Arecae semen (AS, SAS, and FAS) that collected from four provinces were investigated using high-throughput sequencing and internal transcribed spacer 2. Results showed that the phyla Ascomycota (75.45%) and Basidiomycota (14.29%) and the genera Wallemia (7.56%), Botryosphaeria (6.91%), Davidiella (5.14%), and Symbiotaphrina (4.87%) were the dominant fungi, and they presented significant differences in four areas and three processed products (P < 0.05). The α-diversity and network complexity exhibited significant differences in the four sampling locations (P < 0.05), with higher in Yunnan (Chao 1, 213.45; Shannon, 4.61; average degree, 19.96) and Hainan (Chao 1, 198.27; Shannon, 4.21; average degree, 22.46) provinces. Significant differences were noted in the three processed samples; and SAS group had highest α-diversity (Chao 1, 167.80; Shannon, 4.54) and network complexity (average degree, 18.32). In conclusion, the diversity and composition of microbiome on the surface of Arecae semen were shaped by sampling location and processing methods. This work provides details on the surface microbiome of Arecae semen samples and highlights the importance of roles of origin and processing methods in microbiomes, ensuring drug efficacy and food safety.